TRANSFORMASI KESENIAN POJHIÂN KE DALAM PENCIPTAAN KOMPOSISI MUSIK TRADISI INOVASI BERBASIS LOKAL WISDOM - Sugmatimur, Yuddan Fijar; Widianto, Suwandi (Institut Seni Indonesia Surakarta, 2023)
The transformation of Pojian art into the creation of innovative music compositions can be an alternative to regenerate the existance of Pojhian art actors. This effort is to maintain the existence of Pojhian art in the midst of the onslaught of increasingly sophisticated technology, so that it can stimulate the attractiveness of the millennial generation to be proud and take part in the Pojian art which is full of noble values. The purpose of this research is to find out the extent to which the potential of the performance form and song material in Pojian can be exposed to be fresher through the novelty of original musical works. The method used in this research consists of 2 stages, namely; conceptual stage and operational stage. The conceptual stage con- sists of determining objectives, determining musical themes, gathering information, analyzing information, determining instruments, melodies and determining artistic design. The operational stage includes music exploration, notation modification, arrangement variation, music composition, song verse writing, notation writing, artistic design selection and artistic research. There are 3 types of data in this research that are used as measuring instruments, namely; validity, originality of artwork, and novelty. The test subjects in this study were two validators, namely validators of traditional art preservationists to measure the suitability of the appli- cation of the Pojhiân art presentation structure contained in the Gâdhisa ritual and validators of music experts (composers) to measure the originality of the work, and the novelty of the music composition presented.